Testing family-centered, function-focused care in hospitalized persons with dementia. (June 2015) - Boltz, Marie; Chippendale, Tracy; Resnick, Barbara; Galvin, James E
SUMMARY : Aim : Hospital-acquired disability causes decreased quality of life for patients with dementia and family caregivers, and increased societal costs.Materials & methods : A comparative, repeated measures study tested the feasibility and preliminary efficacy of the family-centered, function-focused care intervention (Fam-FFC) in dyads of hospitalized, medical patients with dementia and family caregivers (FCGs).Results : The intervention group demonstrated better activities of daily living and walking performance, and less severity/duration of delirium and hospital readmissions, but no significant differences in gait/balance. FCGs showed increased preparedness for caregiving and less anxiety but no significant differences in depression, strain and mutuality.Conclusion : Fam-FFC presents a possible pathway to meeting the Triple Aim of improved patient care, improved patient health and reduced costs for persons with dementia.